2023
DOI: 10.1002/cpp.2922
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of the Swedish Traumatic Grief Inventory Self‐Report Plus (TGI‐SR+) in bereaved parents

Lonneke I. M. Lenferink,
Iris van Dijk,
Maarten C. Eisma
et al.

Abstract: The International Classification of Diseases Eleventh Edition (ICD‐11), and the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, Text Revision (DSM‐5‐TR), now include prolonged grief disorder (PGD). Since criteria for PGD in both classification systems differ from prior proposed grief disorders and each other, the validation of a single instrument to screen for prolonged grief (PG) symptoms of both new diagnoses is critical for bereavement research and care. Therefore, we evaluated the psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Our second main finding was that, in the whole sample as well as the recently (<6 months) and more remotely bereaved (≥6 months) subsamples considered separately, PGD symptoms formed a unitary factor. This is consistent with prior research showing that PGD symptoms as defined in ICD-11 are best described as forming one dimension (Ashouri & Yousefi, 2023;Boelen & Lenferink, 2020;Kokou-Kpolou et al, 2022;Lenferink et al, 2022Lenferink et al, , 2024. Notably, some other studies have found these symptoms to represent two distinguishable dimensions of separation distress and accompanying symptoms (e.g., Hyland et al, 2024;O'Conner et al, 2023); however, in most of the studies examining the dimensionality, both the one-and two-dimensional models evidenced acceptable fit.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Our second main finding was that, in the whole sample as well as the recently (<6 months) and more remotely bereaved (≥6 months) subsamples considered separately, PGD symptoms formed a unitary factor. This is consistent with prior research showing that PGD symptoms as defined in ICD-11 are best described as forming one dimension (Ashouri & Yousefi, 2023;Boelen & Lenferink, 2020;Kokou-Kpolou et al, 2022;Lenferink et al, 2022Lenferink et al, , 2024. Notably, some other studies have found these symptoms to represent two distinguishable dimensions of separation distress and accompanying symptoms (e.g., Hyland et al, 2024;O'Conner et al, 2023); however, in most of the studies examining the dimensionality, both the one-and two-dimensional models evidenced acceptable fit.…”
Section: Discussionsupporting
confidence: 87%
“…We found no evidence that PGD severity and caseness differed as a function of gender, age, and education. Some other recent studies similarly found no association with gender (e.g., Hyland et al, 2024;Lenferink et al, 2024). Regarding age, Hyland et al (2024) observed that increased age was associated with a lower chance of meeting criteria for PGD in their UK (but not their Irish) sample.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, there are indications that different measures assessing grief intensity correlate very strongly (i.e. correlations ≥ .80) (Lenferink, van Dijk et al, 2023 ). This suggests that different grief measures have more communalities than differences, however caution is warranted when comparing the results across studies using different grief measures and different criteria-sets for prolonged grief (see for discussion: Boelen & Lenferink, 2020 ; Eisma, 2023 ; Lenferink et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%